Perspectives on the Development of Filter Media for Point of Use Water Filters: Case Study of Arsenate Removal - Chigome, Samuel; Andala, Dickson; Kabomo, Moses; Mobegi, Erick (Frontiers in Chemistry, 2022)
The demand for access to clean water will continue to increase as the world population increases. For sustainable development and embracement of technological advancement, it is plausible to consider a filter material development approach that uses locally abundant natural resources as the raw material and nanotechnology techniques for material fabrication. The review and research paper will present a perspective of the authors on how to embrace nanotechnology for filter media development with key focus on the remediation of arsenate. Drinking water contaminated with arsenic is an emerging global challenge. Continuous exposure to drinking water with high levels arsenic could result in several types of cancer. With this in mind, the US EPA in 2001 set 10 ppb as the maximum contaminant level of arsenic from the initial 50 ppb. Therefore, arsenic remediation is key in mitigating these health risks in people residing near water bodies with elevated arsenic levels. Adsorption is considered to be the cheapest. However, from literature, majority of the adsorbents cannot be used in field applications due to challenges associated with low adsorption capacity and a high level of particle leaching into purified water thus posing health dangers. Therefore, it means that many of these adsorbents are economically non-viable. A new chitosan, aluminium, titanium, iron and zirconium (CTS-Al-Ti-Fe-Zr) hybrid was fabricated through the sol-gel process. The material was characterized by scanning electron microscopy, Brunauer–Emmett–Teller and Fourier Transform Infrared spectroscopy before and after adsorption. Batch adsorption properties towards As(V) were separately studied as a function of the effect of adsorbent dose, pH, initial concentration, contact time and competing ions. Characterization results show that the material is a polycrystalline with a specific surface area of 56.4 m2g−1. Further, FTIR and SEM-EDAX showed adsorption of arsenate on the surface of the nanocomposite. Research findings suggest that with only 100 mg of the adsorbent arsenate can be reduced to less than 10 ppb from an initial concentration of 300 ppb respectively. The maximum adsorption capacity for arsenate removal was recorded as 123 mg/g. The presence of SiO32-, CO32-, and HCO3− ions resulted in a slight decline in the adsorption efficiency of arsenate. The equilibrium data fitted well with the Langmuir isotherm 0.99518. Data from the fabricated prototype Point-of-use filter showed that with 60.0 g of the nanocomposite, it is possible to reduce 650 L of drinking water with an arsenate initial concentration of 300 ppb to less 10 ppb. In conclusion, the research findings suggest that the nanocomposite material is capable of removal of arsenate from contaminated drinking water to WHO acceptable levels with a potential to be up scaled for commercial applications.